A printable, unimolecular, core-shell polymer bottlebrush-based signal transducer using solvatochromatic reporting - Zhang, Chenyou; Catt, Samantha; Hawtrey, Tom; Zeng, Ping; Zeng, Haoxiang; Kerai, Simran D.; Cheng, Yen Theng; Hopp, Moritz Philipp; Yang, Qinqin; New, Elizabeth J.; Blasco, Eva; Müllner, Markus (Chemical science, 2026)
The combination of stimuli-responsiveness, colloidal stability and tolerance to changes in concentration and ionic strength into a functional nanoparticle system is challenging. Self-assembled polymer materials remain susceptible to environmental changes, which in turn limit their application potential. Unimolecular architectures like bottlebrush polymers offer enhanced stability and functional compartmentalisation within a single macromolecule. Here, we report the synthesis of a pH-responsive molecular polymer bottlebrush (MPB) featuring a poly[(diisopropylamino)ethyl methacrylate] (PDPAEMA) core, a hydrophilic poly[poly(ethylene glycol) methyl ether methacrylate] (PPEGMA) shell, and naphthalimide-based solvatochromic fluorophores embedded within its core. The PDPAEMA segment imparts pH sensitivity, while the PEGMA shell improves colloidal stability and biocompatibility. The solvatochromic dyes report environmental changes by responding to polarity shifts in the polymer architecture and polymer networks. Our proof-of-concept study promises future application of such unimolecular constructs as nanoscale pH sensors for biomedicine or as functional additives for 3D printing capable of reporting environmental changes within a printed network or (hydro)gel.
Zuerst veröffentlicht: 18 Nov 2025
Gesehen am 23.02.2026